2011
DOI: 10.1007/s10672-011-9185-z
|View full text |Cite
|
Sign up to set email alerts
|

The Continuing Controversy over Right-to-Work Laws in the Early Twenty-First Century

Abstract: This article provides a brief introduction to the ongoing controversy concerning right-to-work (RTW) legislation in the United States. The paper proceeds with the outlining of the major ideological arguments in favor of and in opposition to RTW laws before presenting the taste, free rider and bargaining power hypotheses which has motivated research concerning the economic effects of RTW laws. After reporting the findings of some of the basic empirical research designed to test these hypotheses as well as other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 15 publications
(35 reference statements)
0
15
0
Order By: Relevance
“…Ellwood and Fine (1987) show that unions become less successful in gaining new members through elections and in organizing larger workplaces following RTW passage. Moore (1998) synthesizes many early studies of economics and argues that the range of decline in union membership attributable to RTW laws is between 3-8%, with effects due to both loss of union membership and reduced likelihood of joining unions (see too Devinatz 2011, Eidlin 2018. In total, RTW laws tend to successfully increase the costs of remaining in and joining labor unions.…”
Section: Right To Work Lawsmentioning
confidence: 97%
See 1 more Smart Citation
“…Ellwood and Fine (1987) show that unions become less successful in gaining new members through elections and in organizing larger workplaces following RTW passage. Moore (1998) synthesizes many early studies of economics and argues that the range of decline in union membership attributable to RTW laws is between 3-8%, with effects due to both loss of union membership and reduced likelihood of joining unions (see too Devinatz 2011, Eidlin 2018. In total, RTW laws tend to successfully increase the costs of remaining in and joining labor unions.…”
Section: Right To Work Lawsmentioning
confidence: 97%
“…How do Right to Work laws affect the distribution of economic resources? Stratification scholars working from a power resources theoretical perspective would predict that these laws have inequality inducing consequences (Korpi 1985, Brady and Leicht 2008, Devinatz 2011, Jacobs and Dirlam 2016). Yet surprisingly, the vast majority of empirical research on this topic finds that Right to Work laws have at most a marginal influence on distributional outcomes (Moore 1998, Farber 2005, Hanley 2010, Eren and Ozbeklik 2016, Kogan 2017.…”
mentioning
confidence: 99%
“…The share of "free rider" employees-those who receive union benefits without contributing union dues-in "right-to-work" states varies from a low of 9 percent in Georgia to a high of almost 40 percent in South Dakota (Devinatz 2011). Delaney's (1998) review of the research on the correlates of "free riders" found that women, those with higher education, and white-collar, service sector workers are more likely to free ride.…”
Section: The Effect Of Right-to-work Laws In the United States And Grmentioning
confidence: 99%
“…One proposed policy change in many struggling states is the implementation of a right-to-work (RTW) law, which limits the ability of labor unions to collect "fair share" fees from the workers they represent and influence the conditions of employment for a workplace (Devinatz 2011). In 2012, Indiana became the first state in America to adopt an RTW law since Oklahoma in 2001.…”
Section: Introductionmentioning
confidence: 99%
“…The nine million-job shortfall induced by the late-2007 economic recession and the election of Republican governors, and legislative majorities since 2010, has caused a number of states to rethink policies on employment and income growth. One proposed policy change in many struggling states is the implementation of a right-to-work (RTW) law, which limits the ability of labor unions to collect "fair share" fees from the workers they represent and influence the conditions of employment for a workplace (Devinatz 2011). In 2012, Indiana became the first state in America to adopt an RTW law since Oklahoma in 2001.…”
Section: Introductionmentioning
confidence: 99%